Pengaruh Situational Leadership dan Corporate Culture Terhadap Kinerja Karyawan Dengan Employee Engagement Sebagai Variabel Mediasi - Kristianto, Muhammad Ari Fahlul; Lahindah, Laura (Syntax Corporation, 2025)
This study aims to analyze the influence of situational leadership and corporate culture on employee performance with employee engagement as a mediating variable in PT. PLN (Persero) Project Management Center. The research uses a quantitative approach with a survey design. The research population is all employees of PT. PLN (Persero) Pusmanpro totaled 310 people with a sample of 175 respondents who were selected using the purposive sampling technique. The research instrument was in the form of a questionnaire with a 5-point Likert scale. Data analysis used Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS 3.0 software. The results showed that situational leadership had a significant negative effect on employee performance (β = -0.259, p < 0.002) and employee engagement (β = -0.443, p < 0.000). Corporate culture has a significant positive effect on employee performance (β = 1.011, p < 0.000) and employee engagement (β = 0.777, p < 0.000). Employee engagement had a significant positive effect on employee performance (β = 0.278, p < 0.000). Employee engagement mediated the influence of situational leadership on employee performance negatively (β = -0.671, p < 0.000) and mediated the influence of corporate culture on employee performance positively (β = 0.331, p < 0.000). Corporate culture is the dominant factor that affects employee performance, while inconsistent situational leadership can actually reduce engagement and performance. Employee engagement has proven to be an important mediator in the relationship between corporate culture and employee performance.